The Effectiveness of Numbered Heads Together Technique in Teaching Writing Hortatory Exposition Text - Rizqina Rachman; Vega Hesmatantya (Tell : Teaching of English Language and Literature Journal, 2017)
ABSTRACTWriting skill is considered difficult for students because they get difficult to develop the idea, apply the grammar, do not have any vocabularies. The objective of this research are to describe the effetiveness of Numbered Heads Together technique, to know signficant difference of using NHT compares to talking stick in teaching writing hortatory exposition text. This research was done on April, 13th 2016 to May, 17th 2016. This research used experimental design that the sample used XI-IPA3 as control class and XI-IPA4 as experimental class of SMA Wachid Hasyim1 Surabaya. Based on result of the research, NHT is effective to be used because the result of independent samples test showed that tcount>ttable (4,139>0,172). It means that H1 is accepted, there is significant difference between student’s ability in control and experimental class. Moreover, NHT got positive response from StudentsKeywords : Experimental, NHT, Students’ writing ability, Hortatory exposition